Experimental and theoretical investigation of the reaction of 2,5-diphenyl-1,3-oxazole and 2,5-diphenyl-1,3,4-oxadiazole dimethylamino derivatives with the Vilsmeier reagent - Semenova, O.N.; Galkina, O.S.; Patsenker, L.D.; Yermolenko, I.G.; Fedyunyayeva, I.A. (Functional Materials, 2004)
The 2,5-diphenyl-1,3-oxazole and 2,5-diphenyl-1,3,4-oxadiazole dimethylamino deriva¬tives are widely used as organic luminophores. These compounds are found to be substi¬tuted in the ortAo-position to the dimethylamino group under conditions of the Vilsmeier- Haack reaction. The attack by the POCI3-DMF complex results in formation of the "open" iminium salt which is subjected the isomerization into tetrahydroquinazolinium salt. The substitution reaction directed to the 4 position of the oxazole ring causes formylation. The reactivity of the compounds under investigation and the reaction pathways have been studied using the quantum-chemical semi-empirical methods. The most favorable condi - tions for synthesis of the quinazolinium salts and aldehydes have been determined. The compounds obtained are of considerable interest as the water soluble high-efficiency luminophores.